Deteksi Kebocoran Dan Sumbatan Pada Pipa Menggunakan Sinyal Suara - Tengku Hamzir Muhardillah Yahya; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The pipeline system leads an important role and ubiquitous feature of modern society which is used as one of the high integrity fluid transport function, but has a major problem such as leakage and blockage. Detection methods are typically performed using ultrasonic pressure and wave differences at a relatively high price. The research method used is detection by using sound signal. Sound signal method is smart structural health monitoring that can detect problems quickly and precisely which has the advantage that is cheaper cost. Sound signals are given for leakage, blockage, and joint damage to water and waterless conditions of different sizes and positions. The sound signal data is processed by fast fourier transform and wavelet transform methods. From the test obtained the result increase amount of damage given the greater the amplitude generated with the largest estimation error in full blockage condition with water of 5%.Keywords : Sound signal, leakage, blockage, fast fourier transform, wavelet transform